Analisis Bisnis Proses Keberatan Dan Pengurangan PBB di BAPENDA Kota Palembang - Pangestu, Ridho; Putra, Pacu; Jambak, Muhammad Ihsan; Hardiyanti, Dinna Yunika; Sari, Winda Kurnia; Gumay, Naretha Kawadha (Prodi Sistem Informasi Universitas Dharma Andalas, 2023)
The Internal Control System (ICC) is a crucial workflow in actions and activities that are continuously carried out by superiors and all employees to ensure the achievement of organizational targets through efficient and effective measures, reliability of financial reports, protection of state assets, and compliance with applicable laws and regulations. In the business process of objection and reduction of PBB at the Regional Revenue Agency (BAPENDA) of Palembang City shows that the previous business process has several existing obstacles, such as from existing staff, process time, and in terms of tasks in the business process. Therefore, it is necessary to analyze the business process of objection and reduction of PBB at the Regional Revenue Agency (BAPENDA) of Palembang City. So that the research aims to analyze the suitability of this procedure with SPIP and other inhibiting factors. The method used in this research is the Business Proceses Improvement (BPI) method, which is a method used to analyze the business process of tax objections and UN reductions, and uses the Bizagi Modeler application as a simulation of business process analysis, and uses Streamlining Tools in making improvements to the old business so that it becomes a more effective and efficient business process. Based on the results obtained, it shows that the original business process takes a long time so that new business process recommendations are made. This is intended to make the time required shorter than the old one.